Multicollisions in sponge construction - Alahmad, Mohammad A.; Alshaikhli, Imad Fakhri Taha; Nandi, Mridul (2013)
Cryptographic hash functions take an unfixed size of input and produce a fixed size of an output. A hash function is built using two main components: a compression function and mode of operation. Sponge construction is one of the main operations of modes used in modern cryptographic hash function today. In this paper, we present multicollisions attack in sponge construction. Joux et al. [3] presented multicollision attack in iterated hash function. Our attack is similar to Joux attack but specifically for sponge construction. We showed that multicollisions in sponge construction of messages when the capacity c=n* yields to the same hash digest. Then, we use multicollision attack as a tool to prove that concatenating more than one hash function in order to increase the security level does not yield to more secure hash function.